2018
DOI: 10.3390/jintelligence6010007
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Abilities and Rule Learning: Patterning and Biconditional Discriminations

Abstract: Previous experience with discrimination problems that can only be solved by learning about stimulus configurations enhances performance on new configural discriminations. Some of these effects can be explained by a shift toward increased configural processing (learning about combinations of cues rather than about individual elements), or by a tendency to generalize a learned rule to a new training set. We investigated whether fluid abilities influence the extent that previous experience with configural discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Humans and other animals typically find biconditional discriminations more difficult to acquire than patterning discriminations (Harris & Livesey, 2008; Harris, Livesey, Gharaei, & Westbrook, 2008). The relations between cues in a biconditional discrimination are more complex and difficult to describe via a simple heuristic like the opposites rule (see Baetu, Burns, Yu, & Baker, 2018). Thus, it is debatable whether learning the relations involved in the structure of the biconditional task is as useful as in patterning, where it may be advantageous for overcoming the deleterious effects of summation on negative patterning, in particular (e.g., see Livesey, Thorwart, & Harris, 2011; Thorwart, Uengoer, Livesey, & Harris, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans and other animals typically find biconditional discriminations more difficult to acquire than patterning discriminations (Harris & Livesey, 2008; Harris, Livesey, Gharaei, & Westbrook, 2008). The relations between cues in a biconditional discrimination are more complex and difficult to describe via a simple heuristic like the opposites rule (see Baetu, Burns, Yu, & Baker, 2018). Thus, it is debatable whether learning the relations involved in the structure of the biconditional task is as useful as in patterning, where it may be advantageous for overcoming the deleterious effects of summation on negative patterning, in particular (e.g., see Livesey, Thorwart, & Harris, 2011; Thorwart, Uengoer, Livesey, & Harris, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although Mitchell, Griffiths, Seetoo, and Lovibond (2012) found that the learned predictiveness in one experiment was completely reversible by instructions, others have reported persistent resistance to instructed reversal (Don & Livesey, 2015;Shone, Harris, & Livesey, 2015). Baetu et al (2018) found that improvements in performance completing the second of two successive biconditional discriminations were predicted by measures of fluid ability. Rather than concluding that this effect was based on rule-learning, they argued that this demonstrates flexible use of configural processing among individuals with higher cognitive capacities.…”
Section: Associability and Relational Structure In Learningmentioning
confidence: 99%
“…Both human participants and laboratory animals find learning biconditional discriminations relatively difficult; they are acquired more slowly than linearly solvable discriminations that are matched for presentation of compound cues (Livesey, Thorwart, de Fina, & Harris, 2011;Saavedra, 1975) but also more slowly than positive and negative patterning discriminations Harris, Livesey, Ghareai, & Westbrook, 2008). Baetu, Burns, Yu & Baker (2018) recently argued that biconditional discriminations cannot be solved using a rule. However, there is a relational structure within a biconditional discrimination that can be abstracted and applied to novel stimuli.…”
Section: Rule Complexitymentioning
confidence: 99%
“…Baetu, Burns, Yu, and Baker (2018) recently argued that biconditional discriminations cannot be solved using a rule. However, there is a relational structure within a biconditional discrimination that can be abstracted and applied to novel stimuli.…”
Section: Rule Complexitymentioning
confidence: 99%
See 1 more Smart Citation